A photoelastic investigation of partially debonded rigid line inclusion. (1st March 2022) - Jobin, T.M.; Khaderi, S.N.; Ramji, M.
Abstract: An inverse three-quarters singularity with an oscillatory behavior exists at the tip of a partially debonded rigid line inclusion. The studies on partially debonded rigid line inclusion are hitherto confined to analytical solutions. There exists no work until now that studies partially debonded rigid line inclusions experimentally. In this paper, we experimentally investigate the mechanics of a rigid line inclusion that is bonded to one of its surface. Debonded rigid line inclusion specimens oriented along the direction of loading and perpendicular to the loading direction are considered. Digital photoelastic technique is employed to extract the whole field stress distribution near the debonded inclusion tip. Here, the emphasis is laid on the experimental aspects, starting from the specimen realization to data extraction. The nature of singularity at the tip is investigated, and a multi-parameter stress field equation for a partially debonded rigid line inclusion problem is derived. A complex stress intensity factor is defined at the inclusion tip to quantify the magnitude of singularity and is estimated experimentally using a linear over-deterministic least-squares approach involving the digital photoelasticity. Graphical abstract: